DNA-driven dynamic assembly of MoS2 nanosheets. (6th January 2021) - Amoroso, Giuseppe; Sapelkin, Andrei; Ye, Qingyu; Araullo-Peters, Vicente; Cecconello, Alessandro; Fernandez, Gustavo; Palma, Matteo
Abstract : We demonstrate a strategy to drive the assembly of molybdenum disulfide nanosheets and their disassembly in response to different stimuli. Abstract : Controlling the assembly of molybdenum disulfide (MoS2 ) layers into static and dynamic superstructures can impact on their use in optoelectronics, energy, and drug delivery. Toward this goal, we present a strategy to drive the assembly of MoS2 layers via the hybridization of complementary DNA linkers. By functionalizing the MoS2 surface with thiolated DNA, MoS2 nanosheets were assembled into mulitlayered superstructures, and the complementary DNA strands were used as linkers. A disassembly process was triggered by the formation of an intramolecular i-motif structure at a cystosine-rich sequence in the DNA linker at acidic pH values. We tested the versatility of our approach by driving the disassembly of the MoS2 superstructures through a different DNA-based mechanism, namely strand displacement. This study demonstrates how DNA can be employed to drive the static and dynamic assembly of MoS2 nanosheets in aqueous solution.